Microcontact Printing of Cholinergic Neurons in Organotypic Brain Slices - Steiner, Katharina; Humpel, Christian (Frontiers in Neurology, 2021)
Alzheimer’s disease is a severe neurodegenerative disorder of the brain, characterized by beta-amyloid plaques, tau pathology, and cell death of cholinergic neurons, resulting in loss of memory. The reasons for the damage of the cholinergic neurons are not clear, but nerve growth factor (NGF) is the most potent trophic factor to support the survival of these neurons. Based on a previous study on biomaterials (Ucar et al., 2021, ref 1) we aim to microprint NGF onto semipermeable 0.4 µm pore membranes and couple them to organotypic brain slices of the basal nucleus of Meynert and to characterize neuronal survival and axonal growth. Brain slices were prepared from postnatal day 10 wildtype mice (C57BL6), cultured on membranes for 2-6 weeks, stained and characterized for choline acetyltransferase (ChAT). NGF was microcontact printed in 28 lines, each with 35 µm in width, 35 µm space between them and with a length of 8 mm. As NGF alone could not be printed on the membranes, NGF was embedded into collagen hydrogels and brain slices were placed in the center of these microprints and cholinergic neurons survived. ChAT+ processes were found to grow along the NGF microcontact prints, but also cells migrated. Within the brain slices some form of re-organization along the NGF microcontact prints occurred, especially GFAP+ astrocytes. In conclusion, we provide a novel innovative microcontact printing technique on semipermeable membranes which can be coupled to brain slices. Collagen is used as a loading substance and allows microcontact printing of nearly any protein of interest.